ANALISIS PERLAKUAN AKUTANSI TERHADAP RESTRUKTURISASI KREDIT PADA PT BANK RAKYAT INDONESIA (PERSERO) Tbk CABANG SINJAI UNIT TASSILILU - Suci Putri Astiti; Andi Nurbaeti Jannati (Cross-border, 2021)
The research entitled Analysis of Accounting Treatment of Credit Restructuring at PT Bank Rakyat Indonesia Sinjai Branch Tassililu Unit aims to determine the analysis of accounting treatment and the impact of restructuring for customers at PT Bank Rakyat Indonesia Sinjai Branch Tassililu Unit. The type of research used is descriptive qualitative, which describes the results of direct interviews with the accounting division, credit division and customers aged 50-56 years who carry out credit restructuring. The results showed that the credit restructuring implemented at PT Bank Rakyat Indonesia's Sinjai Branch Tassililu Unit was guided by the Regulation of the Financial Services Authority of the Republic of Indonesia Number 11/PJOK.03/2020, Bank Indonesia Regulation Number 14/15/PBI/2012 Article 54 Paragraph 54 , Indonesian Banking Accounting Guidelines regarding credit restructuring and Statement of Financial Accounting Standards Number 50 regarding liabilities or equity and Number 55 regarding asset measurement (Revised 2014). And 87.59% of customers think that restructuring has a very good impact, 4.17% of customers think it is not good, the remaining 8.24% think that restructuring has no effect.